Lack of correlation between metastasis of human rectal carcinoma and the absence of stromal fibronectin. - Niemczuk, P. (Nature Publishing Group, 1982)
In a retrospective study we have used an immunoperoxidase procedure to localize the glycoprotein fibronectin in human rectal carcinomas, concentrating on tumour invading thick-walled extramural veins. Fibronectin was present in 29 out of 38 cases, in connective tissue stroma, and was not in direct association with the tumour cells, except in areas of necrosis. We found no correlation between the presence or absence of stromal fibronectin and (1) the degree of cellular differentiation within the tumour, (2) tumour progression (Dukes' classification) (3) the subsequent development of metastases and (4) patient longevity. OUr results do not support the conclusions from in vitro studies (Smith et al., 1979) that the metastatic potential of carcinomas may be partly determined by the ability of tumour cells to synthesize pericellular fibronectin. IMAGES: